Case report: A case of novel treatment for retrograde cricopharyngeal dysfunction - Xie, Mengshu; Wen, Hongmei; Dou, Zulin (Frontiers in Neurology, 2022)
Retrograde cricopharyngeal dysfunction (R-CPD) is a recently described disorder characterized by an inability to belch, excessive flatulence, unpleasant gurgling noises, and discomfort in the lower neck, chest, and abdomen. Herein, we describe a case of R-CPD in a 19-year-old man. The patient suffered from flatulence and was unable to belch since birth; auxiliary examination of his digestive system was normal. He was diagnosed with R-CPD based on clinical manifestations and laboratory results. He received an injection of botulinum toxin to the cricopharyngeal muscle under ultrasound, catheter balloon, and electromyographic guidance. His symptoms completely resolved one week after the injection.